The ER Aminopeptidases, ERAP1 and ERAP2, synergize to self-modulate their respective activities - Martín-Esteban, Adrian; Rodriguez, Jesus Contreras; Peske, David; Lopez de Castro, Jose A.; Shastri, Nilabh; Sadegh-Nasseri, Scheherazade (Frontiers in Immunology, 2022)
Critical steps in Major Histocompatibility Complex Class I (MHC-I) antigen presentation occur in the endoplasmic reticulum (ER). In general, peptides that enter the ER are longer than the optimal length for MHC-I binding. The final trimming of MHC-I epitopes is performed by two related aminopeptidases, ERAP1 and ERAP2 in humans that possess unique and complementary substrate trimming specificities. While ERAP1 efficiently trims peptides longer than 9 residues, ERAP2 preferentially trims peptides shorter than 9 residues. Using a combination of biochemical and proteomic studies followed by biological verification, we demonstrate that the optimal ligands for either enzyme act as inhibitors of the other enzyme. Specifically, the presence of octamers reduced the trimming of long peptides by ERAP1, while peptides longer than nonomers inhibit ERAP2 activity. We propose a mechanism for how ERAP1 and ERAP2 synergize to modulate their respective activities and shape the MHC-I peptidome by generating optimal peptides for presentation.